ATOM: A Mobile TOEFL App to Boost Your English Proficiency: ATOM: Aplikasi TOEFL Seluler untuk Meningkatkan Kemahiran Bahasa Inggris Anda - Pangestu, Bagus Aji Agung; Untari, Rahmania Sri (Universitas Muhammadiyah Sidoarjo, 2023)
In the era of Industry 4.0, like today, the role of English language proficiency has become a necessity for everyone. One way to assess someone's English language proficiency is through the TOEFL test. Therefore, there is a need for supporting media to maximize someone's English language proficiency in the TOEFL test. This research aims to develop a TOEFL application as an introduction to education. The method used is R&D as developed by Borg and Gall. This study produced an Android application called